A Cognitive Reformation. (16th October 2019) - Goel, Ashok
Abstract: Although cognitive science started in the 1970s as a multidisciplinary field with the goal of becoming an interdisciplinary one over time, it is now dominated by cognitive psychology. The question becomes whether this matters, and if it does, what should cognitive scientists do about it? I propose that the multidisciplinarity and interdisciplinarity of cognitive science does matter because it leads to potential generation of new ideas, models, and methods. I offer a few recommendations for reforming cognitive science based, in part, on the recent 41st annual meeting of the Cognitive Science Society that sought to reopen cognitive science to minority disciplines comprising cognitive science.